MENCARI ALIRAN BINTANG DI PIRINGAN TEBAL DAN HALO GALAKSI MENGGUNAKAN DATA GAIA DR2, LAMOST DR4, DAN RAVE DR5 - Made Kartika Wijayanti, Ni
Milky Way Galaxy consists of several components: bulge, disk, and halo. Halo of Galaxy comprises dark matter, low-metallicity stars, globular clusters, satellite galaxies, and hypervelocity stars. Globular clusters and satellite galaxies can be disrupted due to tidal force when they are close to galactic center. The stars that unbounded from the globular clusters or satellite galaxies formed stellar streams. At first, the streams can be detected spatially but in billions of years, stellar streams are mixed and should be detected in the phase-space. This Final Project is using astrometric data from Gaia-DR2 and spectroscopic data from LAMOST DR4 and RAVE DR5. The data are cross-matched into Gaia- LAMOST and Gaia-RAVE. Thick disk and halo stars are selected for each of Gaia- LAMOST and Gaia-RAVE. The selection is based on star’s velocity distribution and metallicity. Thick disk stars have probability of thick disk (TD) over thin disk (D) TD/D > 2 meanwhile halo stars have probability of thick disk (TD) over halo (H) TD/H < 0.01. Based on metallicity range, thick disk stars have -1.6 < [Fe/H] < 0.2 meanwhile halo stars have [Fe/H] < -1,6. Data sample are analyzed using velocity and integral of motion spaces such as U vs V , V vs. p U2 + 2V 2, Vaz vs. VE, and Lz vs. L?. Stars in the stellar streams have the same potential orbit so that they can be detected in velocity and integral of motion spaces. Groupings are detected using wavelet transformation and corrected using Monte Carlo simulation. In this final project, there are two stellar streams detected in the thick disk, known as AF06 and Hercules. In the halo, there are four streams detected, known as BB17-1, BB17-2, S1, and N4. Each of the streams is detected in different integral of motion space, depended on the time when the progenitor of the streams mixed into the Milky Way and the position of the stream in the Galaxy.